IMPLEMENTASI TRI HITA KARANA MELALUI AKTUALISASI DANA PUNIA - Krisna Paramita, Anak Agung Gde; Ayu Antari, Dewa; Suryaningrat, Ayu Putri (Pascasarjana Universitas Hindu Indonesia, 2024)
Hindu teachings emphasize that all actions must be based on dharma in order to achieve harmony and happiness. Tri Hita Karana is a Hindu religious teaching that focuses on harmonious relationships with God, fellow humans and the environment. Harmonizing these three relationships will bring happiness. One way to implement this harmonious relationship is by implementing punia funds. Carrying out good dana punia or what is called satwika dana punia is a way of establishing a harmonious relationship, both with God through yadnya, as well as with fellow humans and the surrounding environment. This tri-harmony relationship provides philosophical value in building a foundation, as a form of actualizing Hindu religious teachings both vertically and horizontally.